KEEFEKTIFAN PELAKSANAAN PENANGGULANGAN BENCANA DI KABUPATEN ACEH BARAT DALAM PERSPEKTIF HUKUM BENCANA - Budi Handoyo (Fakultas Hukum, Universitas Samudra, 2019)
Article 4 of West Aceh Qanun No.13 of 2011 about Disaster Management says that the implementation of disaster management aims to provide protection to the public from the threat of disaster, aligning the legislation that already exists, ensure the implementation of disaster management in a planned, integrated, coordinated, and comprehensive, appreciate the local culture, building and public participation. However, in practice the function structure, substance and legal culture in disaster management has not been effective because it is still faced with mIany obstacles that affect the effectiveness. The implementation of disaster management in Aceh Barat District have not been fully implemented yet effective considering the functioning of the three elements of the legal system became a major element of disaster management.In fact, if all three elements of a functioning legal system with another implementation of disaster management can be effective as effective as can be seen in the alignment of the substance elements Qanun No.13 of 2012 on the disaster management with other legislation.Effective functioning legal culture provide an understanding of the legal community as integration through community participation and socialization legislation implemented through institutional legal authorities.Factors which become obstacles in the disaster relief efforts in Aceh Barat District include inadequate institutional performance and disaster management officials, the low awareness of disaster risk and low understanding of both the law and public administration officials to the disaster rules